Role Lord Antasari in Struggle Indonesian Independence 1809-1862 - Burhanuddin Burhanuddin (Jurnal Scientia, 2024)
Lord Antasari No only considered as leader of the Banjar Tribe, he is also leaders of the Ngaju , Maanyan , Siang, Sihong , Kutai , Pasir , Murung , Bakumpai tribes and several ethnic group others who live in regional and inland areas or along the Barito River, both Muslim and Muslim Kaharingan . The research method used is the historical method. The historical method is the process of critically examining and analyzing past historical records and remains. Lord Antasari, born in 1797 or 1809, was the highest leader in the Sultanate of Banjar. He was crowned Panembahan Amiruddin Khalifatul Mukminin in 1862. He died due to lungs and smallpox in Central Kalimantan. The Banjar people's struggle ended in 1905, with Antasari falling in battle against Dutch troops. He was awarded the title of hero national and independence by the Republic of Indonesia in 1968.